Multi‐parametric profiling of renal cell, colorectal, and ovarian cancer identifies tumour‐type‐specific stroma phenotypes and a novel vascular biomarker. (24th July 2017) - Corvigno, Sara; Frödin, Magnus; Wisman, G Bea A; Nijman, Hans W; Van der Zee, Ate GJ; Jirström, Karin; Nodin, Björn; Hrynchyk, Ina; Edler, David; Ragnhammar, Peter; Johansson, Martin; Dahlstrand, Hanna; et al.
Abstract: A novel set of integrated procedures for quantification of fibroblast‐rich stroma and vascular characteristics has recently been presented allowing discovery of novel perivascular and stromal biomarkers in colorectal, renal cell, and ovarian cancer. In the present study, data obtained through these procedures from clinically well‐annotated collections of these three tumour types have been used to address two novel questions. First, data have been used to investigate if the three tumour types demonstrate significant differences regarding features such as vessel diameter, vessel density, and perivascular marker expression. Second, analyses of the cohorts have been used to explore the prognostic significance of a novel vascular metric, 'vessel distance inter‐quartile range (IQR)' that describes intra‐case heterogeneity regarding vessel distribution. The comparisons between the three tumour types demonstrated a set of significant differences. Vessel density of renal cell cancer was statistically significantly higher than in colorectal and ovarian cancer. Vessel diameter was statistically significantly higher in ovarian cancer. Concerning perivascular status, colorectal cancer displayed significantly higher levels of perivascular PDGFR‐β expression than the other two tumour types. Intra‐case heterogeneity of perivascular PDGFR‐β expression was also higher in colorectal cancer. Notably, these fibroblast‐dominated stroma phenotypes matched previously described experimental tumour stroma characteristics, which have been linked to differential sensitivity to anti‐VEGF drugs. High 'vessel distance IQR' was significantly associated with poor survival in both renal cell cancer and colorectal cancer. In renal cell cancer, this characteristic also acted as an independent prognostic marker according to multivariate analyses including standard clinico‐pathological characteristics. Explorative subset analyses indicated particularly strong prognostic significance of 'vessel distance IQR' in T stage 4 of this cancer type. Together, these analyses identified tumour‐type‐specific vascular‐stroma phenotypes of possible functional significance, and suggest 'vessel distance IQR' as a novel prognostic biomarker.